Pharmaceutical efficacy of novel human-origin Faecalibacterium prausnitzii strains on high-fat-diet-induced obesity and associated metabolic disorders in mice - Yang, Meng; Wang, Jing-Hua; Shin, Joo-Hyun; Lee, Dokyung; Lee, Sang-Nam; Seo, Jae-Gu; Shin, Ji-Hee; Nam, Young-Do; Kim, Hojun; Sun, Xiaomin (Frontiers in Endocrinology, 2023)
Obesity and related metabolic issues are a growing global health concern. Recently, the discovery of new probiotics with anti-obesity properties has gained interest. In this study, four Faecalibacte-rium prausnitzii strains were isolated from healthy human feces and evaluated on a high-fat diet-induced mouse model for 12 weeks. The F. prausnitzii strains reduced body weight gain, liver and fat weights, and calorie intake while improving lipid and glucose metabolism in the liver and adipose tissue, as evidenced by regulating lipid metabolism-associated gene expression, including ACC1, FAS, SREBP1c, leptin, and adiponectin. Moreover, the F. prausnitzii strains inhibited low-grade inflammation, restored gut integrity, and ameliorated hepatic function and insulin resistance.Interestingly, the F. prausnitzii strains modulated gut and neural hormone secretion and reduced appetite by affecting the gut-brain axis. Supplementation with F. prausnitzii strains noticeably changed the gut microbiota composition. In summary, the novel isolated F. prausnitzii strains have therapeutic effects on obesity and associated metabolic disorders through modulation of the gut-brain axis.Additionally, the effectiveness of different strains might not be achieved through identical mechanisms.Therefore, the present findings provide a reliable clue for developing novel therapeutic probiotics against obesity and associated metabolic disorders.